The relationship between nesting habitat and hatching success in Caiman latirostris (Crocodylia, Alligatoridae) - Montini, Juan Pablo; Piña, Carlos I.; Larriera, Alejandro; Siroski, Pablo; Verdade, Luciano M. (Phyllomedusa: Journal of Herpetology, 2006)
The Broad-snouted Caiman uses different habitats for nesting; it has temperature-dependent sex determination (TSD) and nesting habitat selection by females could affect sex and other hatchlings characteristics. Here we evaluated reproductive parameters in three nesting habitats: forest, savanna, and floating vegetation. We collected 154 caiman nests during the summer of 2001-2002. Since natural incubation could mask possible clutch-effects, eggs were collected soon after oviposition and artificially incubated. We found that eggs laid in the forest were wider than those laid in savanna, hatching success varied, decreasing from floating vegetation to forest. As egg width is positively correlated to female body size, the present results suggest that female body size could be related to nesting habitat use in Caiman latirostris. However, there were no differences in hatchling size among nesting habitats.